Stress Indicator, Carcass Composition, and Meat Cholesterol of Kampung-Broiler Crossbred Chicken Treated By Different Stocking Density - Nugraha, Bayu Adhitya; Afnan, Rudi; Darwati, Sri; Suryati, Tuti (ANIMAL PRODUCTION, 2016)
This study aimed to investigate the effect of stocking density on stress indicator, carcass composition, and meat cholesterol content of kampungâbroiler crossbred chicken. Anamount of 90 DOCs of crossbred kampung-broiler (KB) were placed into 9 plots sized 1x1 m2 in semi closed house that consist of 3 stocking densities 8, 10 and 12 birds m-2 and respectively 3 replicates. The chickens were fed commercial broiler feed. Approximately Â± 30% roosters slaughtered for analysis of malondialdehyde, carcass quality, and meat cholesterol. Malondialdehyde, carcass composition, and meat cholesterol was completely randomized designed with different stocking densities treatments and three replicates. Data was analyzed using analysis of variance (ANOVA) and had previously been tested for requirement of variance test assumption. Data of temperature humidity index (THI) was descriptively explained. The results showed that the effect of different stocking densities on stress indicator reflected by THI value and MDA content, carcass composition (percentage of carcass and abdominal fat weight), and cholesterol level were not significant. The different of stocking densities (8, 10 and 12 birds m-2) did not affect the stress indicators reflected by THI and MDA level, carcass composition and meat cholesterol level. Kampung-broiler crossbred chicken could develop at 8, 10 or 12 birds m-2 densities since the lower of abdominal fat and meat cholesterol were resulted